Northwest History. Forest Fires (Cont'd). (1936)
Rush 1000 Men To Fire Lines: 300 From Spokane By Bus To Flathead Forests.: Wind Aids Flame: Triple Blaze Is Opposite Glacier Park, Near Columbia Falls.